South Africa : Financial Sector Assessment Program-Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2022)
The economy recovered strongly in 2021, following an unprecedented real output contraction in 2020. However, the outlook remains precarious amidst projected future low growth, high unemployment and adverse debt dynamics, and the recovery pace is unlikely to be sustained. Ample buffers allowed the financial system to handle the COVID-19 shock relatively well, but domestic and external downside risks remain substantial-with potential implications for asset quality, profitability, and solvency.